2010
DOI: 10.1002/ejic.201000533
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Steric and Electronic Factors of (Arylsulfonyl)phosphane‐Palladium Catalysts in Ethene Polymerization

Abstract: (Arylsulfonyl)phosphane ligands, o-Ar 2 PC 6 H 4 SO 3 H in which Ar is phenyl (Ph), naphthyl (Np), phenanthryl (Pa), or anthracenyl (An) were prepared. These bulky phosphanes were used to generate phosphanepalladium complexes [(o-Ar 2 -PC 6 H 4 SO 3 )PdMe(pyridine)]. These complexes catalyze eth-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
1
40
2
1
Order By: Relevance
“…[19] However, Gates et al have also shown that replacing a CH 3 fragment by a CF 3 fragment on the diimine leads to a significant activity increase, thus hinting that electron-deficient ligands result in more active catalysts. [20] In a previous study, [13] we demonstrated that catalysts based on phenantryl, naphtyl, and anthracenyl moieties are less active than catalyst 2 a.The difference in phosphane basicities between phenyl, naphtyl, anthracenyl, and phenantryl-based ligands is expected to be small in comparison to the large range of basicities assessed in this study. In our case, it is necessary to clarify whether phosphane s-bonding ability is truly at stake.…”
mentioning
confidence: 45%
See 4 more Smart Citations
“…[19] However, Gates et al have also shown that replacing a CH 3 fragment by a CF 3 fragment on the diimine leads to a significant activity increase, thus hinting that electron-deficient ligands result in more active catalysts. [20] In a previous study, [13] we demonstrated that catalysts based on phenantryl, naphtyl, and anthracenyl moieties are less active than catalyst 2 a.The difference in phosphane basicities between phenyl, naphtyl, anthracenyl, and phenantryl-based ligands is expected to be small in comparison to the large range of basicities assessed in this study. In our case, it is necessary to clarify whether phosphane s-bonding ability is truly at stake.…”
mentioning
confidence: 45%
“…[4i] 2b, [13] 2 c, [13] , and ligand 1 h [14] were already described in the literature, but ligands 1 d, 1 e and 1 g, and catalysts 2 b-lut, 2 d-lut, 2 g-lut, 2 hlut were prepared for the first time for this study. We purposely decided to concentrate our attention to lutidine complexes (or pyridine complexes for catalysts already reported), because we found that DMSO complexes (e.g., 2 h-DMSO) were difficult to isolate in a pure form due to the difficulty of evaporating DMSO.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations